A form error evaluation method of honeycomb core surface. (30th September 2022) - Qin, Yan; Kang, Renke; Wang, Yidan; Sun, Jiansong; Dong, Zhigang
Highlights: A form error evaluation method of honeycomb core surfaces is proposed. Reticular surface form extraction of honeycomb core is achieved. The accuracy of form extraction is verified ±7 μm by simulated honeycomb surface. Abstract: Form error evaluation of the machined honeycomb surfaces has the power to deliver tremendous benefits to improve the machining accuracy and guide the assembly process. The line laser measurement can meet the high-resolution requirement for thin-walled honeycomb cell walls, but faces a high proportion of noise data consisting of burrs and outliers. In this paper, dimensionality reduction combined with random sample consensus or regression analysis is adopted to distinguish the irregular noise from the measurement data. A directional extraction of honeycomb core surface form based on locally weighted regression is proposed. A highly realistic honeycomb surface simulation method is established to solve the lack of honeycomb benchmarks. The simulation experiment shows that the accuracy of the proposed method is ±7 μm. The comparison experiment with coordinate measuring machine demonstrates the surface form RMS error differences for the polygonal and curved honeycomb by the two method are 7 μm and 19 μm, respectively.